Exposure of Xenogeneic Biomaterial to the Oral Environment and Its Impact on Tissue Healing of Immediate Dental Implants: A Case–Control Study - Carvalho, Valessa F.; Garcez-Filho, João; Okamoto, Roberta [UNESP]; Frigério, Paula B. [UNESP]; Santos, Priscila L.; Novaes Junior, Arthur B.; Messora, Michel R.; Taba Jr, Mario (MDPI, 2025)
Featured Application: The potential application of intentionally exposing xenogeneic bone may benefit immediate implant placement in molar areas in specific conditions when a flapless approach with an intact buccal wall is granted. Outcomes after implant placement include maintenance of bone stability (both vertically and horizontally), at least 2 mm of keratinized mucosa around implants, and uneventful healing processes. This study evaluated the clinical and tomographic outcomes of socket healing. Immediate implants were placed in the molar area, and the gap was filled with either deproteinized bovine bone mineral (B) or collagen matrix (BM), n = 14/group. Scores of epithelization healing, immunoassay for VEGF, IL-1β, and FGF from wound exudate, keratinized mucosa variation (ΔKM), and bone levels were evaluated. The B group had slower tissue maturation than BM (p < 0.05), but gingival epithelialization was similar (p > 0.05). At the restorative phase, the B group exhibited greater ΔKM at prosthesis installation—1 to 2 months of postoperative (increase of 0.29 mm) compared to the BM group (reduction of −1.5 mm) (p < 0.05). Inflammatory tissue responses as well as vertical and horizontal bone remodeling were similar (p > 0.05). Crestal bone remodeling was limited to less than 0.8 mm for both groups. Taken together, the B and BM groups behaved similarly and promoted stable conditions for biomaterial incorporation in the socket healing after immediate implant placement in molar areas.
Keywords: alveolar bone loss; biomaterials; bone substitute; dental implant; keratin; molar area; soft tissue therapy